The Effectiveness of Using Memrise to Enhance the English Speaking Skills of Thai Students - Muhammad Zhidan Akbar; Rita Harisma (Journal of Practice Learning and Educational Development, 2026)
Speaking stands out as a core skill for English as a Foreign Language (EFL) learners because it lets them share ideas and actually connect. Still, at Darul Ma'arif School Foundation in Satun, Thailand, I noticed a clear pattern: eighth graders struggled with English speaking. The issues popped up in four main areas—limited vocabulary, shaky pronunciation, slow fluency, and grammar mistakes.To tackle these challenges, I used the Memrise app and set up a quantitative study with a quasi-experimental design. One group of 18 eighth graders—all students in that grade—took a speaking test before and after using Memrise. The test focused on pronunciation, vocabulary, fluency, and accuracy, checked with an analytical rubric. After collecting the scores, I analyzed them using descriptive statistics and a paired-sample t-test.The results told a strong story. Average speaking scores jumped from 10.78 before Memrise to 14.94 after—a boost of 4.16 points. The t-test showed significant improvement, t(17) = 12.41, p < .001, with a huge effect size (Hedges' g = 2.79). Breaking this down, pronunciation improved the most, then accuracy, followed by fluency and vocabulary. All in all, Memrise truly helped these EFL students speak better English. In this Thai school setting, Memrise proved itself as a powerful Mobile-Assisted Language Learning (MALL) tool.